Analisis Yuridis Kritis Perlindungan Hukum Jemaah Haji Plus yang Gagal Berangkat karena Pembatalan oleh Travel X Surabaya - Irbah Maysun Anwar; Sri Maharani M.T.V.M (Yustisia Tirtayasa, 2022)
Implementation of the hajj pilgrimage, especially in plus hajj pilgrimage travel, still has incompatibility in the fulfillment of achievement as business actors, such as Travel X in Surabaya that does not fulfill its achievement to the Hajj pilgrims plus as consumers, as mutually agreed in the hajj departure agreement. This has violated several articles in Act Number 8 of 1999 concerning Consumer Protection. This study aims to identify and analyzing the forms of violations by Travel X Surabaya to their pilgrims as well as forms of legal protection for hajj pilgrims plus who failed to leave due to the cancellation by Travel X Surabaya. This research is a normative juridical with the statutory approach, case approach and theoretical approach. Data in this study were obtained from official documents, books related to research objects, research results in the form of reports, theses, legislation and interviews. The results of this study showed that Travel X Surabaya has violated the rights of hajj pilgrims plus, which is the cancellation of hajj departure. Legal protection to hajj pilgrims plus who are failed to leave because due to the cancellation by Travel X Surabaya is carried out through non-litigation way by using the negotiation. The settlement of the non-litigation is one of legal protection for hajj pilgrims plus that is carried out through non-litigation way has been regulated in Act Number 8 of 1999 concerning Consumer Protection